PENGEMBANGAN MODUL BERBASIS KONSTRUKTIVISME DENGAN TEKA TEKI SILANG PADA MATA PELAJARAN TAFSIR KELAS X MAN 2 TANAH DATAR - Kasnida, Kasnida (El -Hekam, 2019)
The problem in this research is related to the absence of teaching materials in the form of modules that can stimulate student creativity in the learning process and students have not been able to solve problems because the learning process only takes one direction (teacher centered). This is because in addition to the limited availability of teaching materials for interpretation and teaching materials available only meet cognitive and intellectual aspects, besides the teacher who is expected to be a facilitator is also not able to provide solutions in overcoming the problem due to limited time and funds. In fact, there are only a limited number of learning resource books available in the library and the material contained in the book is difficult for students to understand, the material being studied is lacking in interpretation. This study aims to obtain a product in the form of Constructivism-Based Modules in Class X MAN 2 Land Interpretation Subjects that are valid, practical, and effective. The type of research used is research and development. This study uses a 4-D development model consisting of four development steps, namely: define, design, and develop. The Learning Module is validated by 4 validators. Then the module was tested limited to 40 students of class X IIK.2 MAN 2 Tanah Datar. The data of this study are primary data obtained from the results of validity by the validator, the assessment of practicality by the teacher and students, and testing the effectiveness by students. Based on the research conducted, it produced the Tafsir learning module on the Historical Interpretation of the Period of the Prophet Muhammad, Friends, Tabiin and Tadwin. The resulting modules are categorized as very valid with an average percentage rating of 82% based on validator ratings. The resulting modules are very practical with an average percentage rating of 88%. The form of module use based on the benefits obtained from the effectiveness of learning time and student learning outcomes shows above the Minimum Mastery Criteria (KKM) with an average of 90%, It can be concluded that the interpretive learning module developed in the Historical Interpretation material during the period of the Prophet Muhammad SAW, Friends, Tabiin and Tadwin for class X MAN 2 Tanah Datar is valid, practical, and effective.